Sewers : rehabilitation and new construction : repair and renovation - Read, Geoffrey F.; Vickridge, Ian G. (Elsevier/Butterworth Heinemann, 1997)
This, the first of two volumes, gives a comprehensive treatment of the civil engineering work relating to sewers and emphasises the practical aspects of repair and renovation. A considerable amount of theoretical work already exists on this subject. However this book is unique in meeting the engineer's need for up-to-date information on the application of theory and incorporates some important recent developments in the field.The technical aspects of survey and access are dealt with in some detail and the book also provides fundamental data on hydraulics, structural assessment and the.